The dynamic relationships between cash and futures market: the Malaysian experience under a shift from flexible to fixed exchange regimes - Wong, Mei Foong; Goh, Han Hwa; Thai, Siew Bee; Ong, Tze San (Serials Publications, 2015)
The purpose of this study is to examine the dynamic relationships between the Kuala Lumpur Stock Exchange Composite Index (KLSE CI) (currently known as FTSE Bursa Malaysia KLCI) and the Kuala Lumpur Stock Exchange Composite Index Futures (KLSE CI Futures), spot month futures contract under a shift from flexible to fixed exchange regimes. The VAR model of Johansen-Juselius multivariate cointegration test, multivariate Granger-Causality test are applied to capture the dynamic linkages between KLSE CI and KLSE CI Futures in the periods of pre- and during the Asian currency crisis under flexible exchange regime and after the crisis fixed exchange regime. The empirical results of this study display that the KLSE CI and KLSE CI Futures are cointegrated and there is long run causality between KLSE CI and KLSE CI Futures in the three sub-sample periods. In the short run, there are evidences of contemporaneous causality running between the variables. The result exhibits that only the KLSE CI does "Granger" causes the KLSE CI Futures in the first sub-sample period. In the second sub-sample period, the KLSE CI Futures "Granger" causes the KLSE CI. In the third sub-sample period, the result displays that the KLSE CI "Granger" causes the KLSE CI Futures. As a conclusion, this study shows that the KLSE CI Futures leads the KLSE CI, especially during the crisis under flexible exchange regime, which implies that KLSE CI Futures has some predictive power for the KLSE CI.